Brief report of virtual clinician research tools for tobacco dependence or dyslipidemia. (September 2017) - Williams, Geoffrey C; Lowenstein, Lisa; Cox, John F; Patrick, Heather; Adams, Michael Jacob; Block, Robert C; Rigby, C Scott
Health avatars were created to deliver previously tested live interventions for tobacco dependence and cholesterol management. The exploratory aims were to develop and test whether the avatar can be reliably assessed for autonomy supportiveness using the Health Care Climate Questionnaire and estimate the mean changes in motivation variables and correlate the avatars' autonomy supportiveness with the motivation variables and health outcomes. The avatars were found to be reliably assessed for autonomy supportiveness on the Health Care Climate Questionnaire. Autonomy support was positively correlated with the change in motivations and reduction in low-density lipoprotein. These findings suggest that health avatars may be tested in clinical trials.